1986
DOI: 10.1099/0022-1317-67-4-671
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Scrapie-associated Fibril (SAF) Proteins Using Anti-SAF Antibody in Non-purified Tissue Preparations

Abstract: SUMMARY Antisera raised to scrapie-associated fibril (SAF) proteins were used to detect scrapie-specific polypeptides in three different non-purified brain preparations: a synaptosomal-mitochondrial fraction, 20% brain homogenate and 20% brain homogenate extracted with Sarkosyl. The concentration of SAF proteins in the preparations was greater than the quantity of SAF as detected by negative stain electron microscopy. This suggests that not all of the protein exists in the form of SAF. An immunologically react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 22 publications
2
51
1
1
Order By: Relevance
“…Affinity-purified immunoglobulins from animals immunised with PrP27 -30 detect a form of this protein in extracts of scrapie-infected brain and uninfected brain which has an apparent mol. wt of 33 000-35 000, significantly larger than (Oesch et al, 1985;Manuelidis et al, 1985;Rubenstein et al, 1986). This PrP 33-35 protein in homogenates of uninfected hamster brain is completely degraded by proteinase K (Oesch et al, 1985;Rubenstein et al, 1986) and neither fibrils nor protein are found in fractions of uninfected brain prepared by the methods developed to isolate SAF.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Affinity-purified immunoglobulins from animals immunised with PrP27 -30 detect a form of this protein in extracts of scrapie-infected brain and uninfected brain which has an apparent mol. wt of 33 000-35 000, significantly larger than (Oesch et al, 1985;Manuelidis et al, 1985;Rubenstein et al, 1986). This PrP 33-35 protein in homogenates of uninfected hamster brain is completely degraded by proteinase K (Oesch et al, 1985;Rubenstein et al, 1986) and neither fibrils nor protein are found in fractions of uninfected brain prepared by the methods developed to isolate SAF.…”
Section: Introductionmentioning
confidence: 97%
“…wt of 33 000-35 000, significantly larger than (Oesch et al, 1985;Manuelidis et al, 1985;Rubenstein et al, 1986). This PrP 33-35 protein in homogenates of uninfected hamster brain is completely degraded by proteinase K (Oesch et al, 1985;Rubenstein et al, 1986) and neither fibrils nor protein are found in fractions of uninfected brain prepared by the methods developed to isolate SAF. This evidence can be used to support a model for the pathogenesis of SAF in which scrapie infection induces the proteolysis of PrP33 -35 to PrP27 -30 and that it is this latter, abnormal by-product of infection which then polymerises into the characteristic disease-specific fibrils ( Figure 4A).…”
Section: Introductionmentioning
confidence: 97%
“…One antibody was generated by injecting a rabbit with antigen derived from sodium dodecyl sulfate-polyacrylamide gel electrophoresis-purified PrP-res from brains of mice inoculated with the ME7 strain of scrapie. 17,31 The other antibody (R27) was to a synthetic peptide corresponding to residues 89-103 of the complete mouse PrP amino acid sequence. 28 Slides were incubated in primary antibody overnight at 4 C, rinsed 3 times in Automation buffer, then held in the buffer at 37 C for 30 min.…”
Section: Sheep Tissuesmentioning
confidence: 99%
“…PrP-res forms insoluble aggregates and is partially resistant to proteinase K (PK), which removes ϳ67 amino acid residues (6 -7 kDa) from the N terminus (1,(3)(4)(5). These differences in biophysical properties most likely reflect different conformations of the two protein isoforms.…”
mentioning
confidence: 99%